Impact of Underground Gold Mining on Soil Chemistry and Biology: Indigenous Microbe-Driven Rehabilitation? - Fahikasari, Indah; Wulandari, Dewi; Widiastuti, Happy; Zarate, Jocelyn T. (Jurnal Biologi Papua, 2025)
Gold mining boosts Indonesia's GDP and exports. However, gold mining changes soil chemical and biological qualities, and therefore harming the environment. Thus, rehabilitating post mining land using environmentally friendly and chap method are essential for soil and ecosystem health. Nitrogen (N), and phosphorus (P) are the most limiting factors in degraded mining area. Azotobacter sp. and Rhizobium sp. are well-known in assisting plant by providing N. Paraserianthes falcataria is well-known as a fast-growing tree species that have good symbiosis with Rhizobium sp. This study examines the chemical and biological effects of underground gold mining on soil and the ability of indigenous Azotobacter sp. and Rhizobium sp., to improve the soil of post gold mining under greenhouse condition. Soils were sampled from natural forest (NF), tailing (T), and 3 different ages of rehabilitated area: 1 year old, 2 year old, and 5 year old. According to this study, gold mining negatively effect on soil organic carbon and nitrogen levels. One Rhizobium sp. isolate and 12 Azotobacter spp. isolates were found in post mining soil. All Azotobacter spp. isolates fixed nitrogen by NFB test and produced IAA. All Azotobacter spp. was determined as gram negative bacteria. A greenhouse study found that Azotobacter sp. inoculation with 10% compost improved the soil quality by increasing soil organic carbon, soil N, soil available P, and exchangeable K. Therefore, this improvement on soil condition increased seedlings height, diameter, and biomass growing in gold tailings soil. These findings highlight the necessity of employing indigenous microorganisms and organic materials to improve soil quality and plant growth on former gold mining areas.